2018
DOI: 10.1111/cns.12983
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin inhibits microglial activation and neuroinflammation by suppressing NLRP3 inflammasome activation in APP/PS1 transgenic mice

Abstract: SummaryBackgroundActivated microglia‐mediated inflammation plays a key role in the pathogenesis of Alzheimer’s disease (AD). In addition, chronic activation of NLRP3 inflammasomes triggered by amyloid β peptide (Aβ) in microglia contributes to persistent neuroinflammation. Here, the primary goal was to assess whether Dihydromyricetin (DHM), a plant flavonoid compound, is effective therapies for AD; it is crucial to know whether DHM will affect microglial activation and neuroinflammation in APP/PS1 transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 36 publications
1
47
1
Order By: Relevance
“…NLRP3 and NFkB signalling pathways were shown to activate upon HH exposure [22] supports our observation where we showed their up regulation in DG. Reduction in BDNF dependent neurogenesis was simultaneous with induction in NLRP3 dependent in ammation similarly shown earlier [72]. Dramatic increase in levels of pro-in ammatory cytokines followed by microglial activation made it imperative to target in ammatory pathways in an attempt to rescue brain neurogenic capability.…”
Section: Discussionsupporting
confidence: 68%
“…NLRP3 and NFkB signalling pathways were shown to activate upon HH exposure [22] supports our observation where we showed their up regulation in DG. Reduction in BDNF dependent neurogenesis was simultaneous with induction in NLRP3 dependent in ammation similarly shown earlier [72]. Dramatic increase in levels of pro-in ammatory cytokines followed by microglial activation made it imperative to target in ammatory pathways in an attempt to rescue brain neurogenic capability.…”
Section: Discussionsupporting
confidence: 68%
“…Among microglia, M2 microglia reportedly express NEP and IDE and reduce Aβ plaques (Shimizu et al, ). Recently, there are a few known agents such as PF‐3845, sarsasapogenin‐AA13, and dihydromyricetin, which promoted M2 microglial and inhibited M1 microglial polarization, leading to the memory recovery in traumatic brain injury and AD models (Feng et al, ; C. Huang et al, ; Tchantchou et al, ). Furthermore, dihydromyricetin promoted the clearance of Aβ and expression of NEP in APP/PS1 transgenic mice brain (Tchantchou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This causes an overall decrease in the levels of APP that can be used to produce Aβ, thereby indirectly reducing Aβ production. Furthermore, studies also showed that DMY can increase the expression of neprilysin (NEP) (Feng et al, 2018). NEP is a M13 zinc metalloproteinase family protein that can cleave Aβ peptide bonds to decompose Aβ (Kanemitsu et al, 2003;Hersh and Rodgers, 2008).…”
Section: Myr and Dmy Interact With Aβ To Exert Anti-ad Effectsmentioning
confidence: 99%